PENGARUH POLA ASUH ORANG TUA DEMOKRATIS TERHADAP PEMBENTUKAN KONSEP DIRI PADA SISWA MAN 1 KABUPATEN GORONTALO - Salahudin Liputo; Reza Idrus (Elsia: Jurnal Psikologi Manusia, 2022)
Democratic parenting is a form of parenting style that pays attention to and respects children's freedom, there is dialogical communication between children and parents, and there is a warm attitude shown by parents to their children. Parenting parents have an important role in efforts to form self-concept, the formation of adolescent self-concept is inseparable from the application of democratic parenting, which applies two-way communication, therefore the formation of self- concept will be created from the interaction between parents and their children. This research aims to determine whether there is an influence between democratic parenting styles on students' self-concept at MAN 1 Gorontalo Regency. This research uses quantitative methods. The  sample  amounted  to  54  students.  The  sampling  technique  used  is  cluster  random sampling. Sources of data in this study were students measured using the democratic parenting style scale and the self-concept scale. Data analysis using simple linear regression technique. The results show a value of 224. This value is greater than 0.05 and it can be seen that the calculated F value is 1.511, meaning that the higher the democratic parenting pattern, the higher the self-concept in adolescents, on the contrary, the lower the parenting style of parents. democratic, it will be accompanied by a lower self-concept in the students of MAN 1 Gorontalo Regency